The Application of Necessity in Medical Treatment: An Islamic Biomedical Perspective (Bangladesh Journal of Medical Science, 2021)
This research paper examines the concept of ‘necessity,’ which derives its origin both in Islamicand common law and transcended progressively into medical law. Many aspects of medicaland civil law remained closely related to each other, like ‘the concept of duress’, ‘self-defense’and other aspects of human activities are embedded in both the systems. Likewise, the commonlaw generally allows almost all forms of treatment, whereas Islamic law permits it, when itessentially saves one’s life. All forms of medical treatments are freely and readily available toovercome sterility dilemmas in western countries, whereas in Islamic law some of the moderninterventional techniques and genetic engineering are disregarded as per Shariahinjections.Whereas, Islam does approve necessary measures to sustain sound and good health, since it isconsidered a part of one’s obligations. Hence, its sustenance senses the subjects to avoid fromundue pains and sufferings. For this purpose, medications and medical treatment is considered arecognized mode in Islamic law. Therefore, on one hand, this research paper presents argumentsin favor of medical treatment, while, on the other hand, it will argue the evidences given byclassical and contemporary scholars in favor of medical treatment within the framework ofShariah. This may attract the essence of Shariahdoctrine of necessity.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.24-32